Mitogenomics supports the monophyly of Mysidacea and Peracarida (Malacostraca). (21st July 2022) - Höpel, Christoph G.; Yeo, Darren; Grams, Markus; Meier, Rudolf; Richter, Stefan
Abstract: Here, we provide the first complete mitochondrial genomes for two higher taxa of Peracarida, Lophogastrida and Stygiomysida. We examined Lophogaster typicus as a representative of Lophogastrida and Spelaeomysis bottazzii as a representative of Stygiomysida. Both mitogenomes have all typical metazoan genes (13 protein‐coding genes, two ribosomal RNA genes and 22 transfer RNAs). The mitogenomes have a length of 15, 076 bp in L. typicus and 14, 806 bp in S. bottazzii. Gene order differs markedly from the hypothetical pancrustacean/malacostracan ground pattern in both species, and in L. typicus, all genes were encoded on the heavy strand. This is the first time this is described for a crustacean. We also reconstruct eumalacostracan phylogenies using a data set consisting of 98 species based on alignments comprising all protein‐encoding genes as well as the protein‐encoding genes and the two ribosomal RNAs. We find support for the monophyly of Mysidacea based on species from all three higher taxa (Mysida, Lophogastrida, Stygiomysida). Moreover, our analyses also support a monophyletic Peracarida with Amphipoda or Amphipoda + Mysidacea as the sister group to the remaining Peracarida.